2007
DOI: 10.1111/j.1464-410x.2007.07339.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐blockers improve chronic ischaemia of the lower urinary tract in patients with lower urinary tract symptoms

Abstract: bladder was filled slowly (50 mL/min) with 0.2 M KCl, which resembles the osmolarity of concentrated urine, and evaluated by cystometry. In parallel, TRCDUS and measurement of the CPD of the LUT were performed. The patients with LUTS were then treated with daily α -blocker (0.4 mg tamsulosin) for 5 weeks and urodynamic variables as well as perfusion were evaluated again. RESULTSIn the healthy men, perfusion of the LUT increased considerably (157%) during filling of the bladder to a mean ( SD ) maximum cystomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 39 publications
5
85
0
3
Order By: Relevance
“…Increased vascular perfusion of the lower urinary tract especially the prostate or bladder neck can result in a beneficial therapeutic effect and decrease LUTS (19).…”
Section: Discussionmentioning
confidence: 99%
“…Increased vascular perfusion of the lower urinary tract especially the prostate or bladder neck can result in a beneficial therapeutic effect and decrease LUTS (19).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that perfusion is reduced in LUTS patients and increases to almost normal levels after α1-blocker treatment, suggesting that treatment improved perfusion in the lower urinary tract (16). However, in the aforementioned work, blood flow at the dome and the posterior wall was not investigated, while perfusion was not measured during bladder emptying.…”
Section: Commentsmentioning
confidence: 97%
“…In addition, these drugs improve LUTS without bladder outflow obstruction. Pinggera and colleagues [Pinggera et al 2008a] reported that α 1 -AR antagonists improved bladder blood flow and symptoms in patients with LUTS, and suggested that these drugs might ameliorate LUTS by increasing bladder blood flow.…”
Section: Mouse Modelmentioning
confidence: 99%